The melting column as a filter of mantle trace‐element heterogeneity - Bo, T; Katz, R; Shorttle, O; Rudge, J (American Geophysical Union, 2018)
The observed variability of trace‐element concentration in basaltic lavas and melt inclusions carries information about heterogeneity in the mantle. The difficulty is to disentangle the contributions of source heterogeneity (i.e., spatial variability of mantle composition before melting) and process heterogeneity (i.e., spatial and temporal variability in melt transport). Here we investigate the end‐member hypothesis that variability arises due to source heterogeneity alone. We model the attenuation of trace‐element variability introduced into the bottom of a one‐dimensional, steady‐state melting column. Our results show that the melting column can be considered to be a filter that attenuates variability according to the wavelength of heterogeneity, the partition coefficient of the trace element, melt productivity and the efficiency of melt segregation. We further show that while the model can be fit to the observations, this requires assumptions inconsistent with constraints on the timescales of magma assembly. Hence, we falsify the end‐member hypothesis and, instead, conclude that observed variability requires heterogeneity of melt transport. This might take the form of channels or waves and would almost certainly interact with source heterogeneity.